Mexico and climate change: A horizon of its own, between denial and prescriptions (Research, Society and Development, 2026)
In recent years, numerous scientific studies have analyzed in depth the global environmental crisis and the impacts associated with climate change. This phenomenon has also prompted the creation of multiple international treaties and mechanisms aimed at addressing it, although the results have been limited. Despite multilateral efforts, the global paradigm remains strained by the persistence of climate denialism and the influence of economic and political interests that hinder collective action. This article aims to examine the current landscape of climate change from both international and national perspectives. It identifies the environmental and climate change public policy position of the United States of America, given its significant regional leadership, and reflects on the strategic position of Mexico. The main findings reveal an international context characterized by a dual dynamic: while the influential neighboring country, the United States of America, reinforces climate change denialism and withdraws from international commitments, multilateral organizations and international courts are strengthening a robust legal framework in favor of climate action. At the national level, Mexico displays an uncertain and contradictory environmental public policy stance. The article is developed from a critical perspective, based on documentary analysis, review of indicators, specialized reports, and relevant media coverage that help to highlight recent trends and actions. The proposal section adopts a public policy approach in order to outline the basis for a feasibility analysis.